2012
DOI: 10.1038/onc.2012.320
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β5 contributes to the tumorigenic potential of breast cancer cells through the Src-FAK and MEK-ERK signaling pathways

Abstract: Cancer progression, response to therapy and metastasis depend on tumor microenvironment. Integrins are cell adhesion receptors that mediate interactions of cells with extracellular matrix (ECM). The αv-β-family of integrins contributes to tumorigenesis, response to therapy and cancer-stem cell biology. Thus, understanding the function of specific integrins in cancer is critical for development of therapeutic approaches targeting integrins. The study investigated the role of integrin β5 in breast carcinomas by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 48 publications
9
118
1
Order By: Relevance
“…Qualitative and quantitative alterations in O-and N-glycosylation in Integrins are consistent features of malignancies (32). Integrins promote various adhesion-dependent effects in tumor cells, including proliferation, survival, migration, and invasion through focal adhesion kinase (FAK) signaling cascades (33)(34)35). FAK phosphorylation is considered to be one of the initial steps that allows binding of Src and Fyn for further phosphorylation leading to signaling cascade (14,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative alterations in O-and N-glycosylation in Integrins are consistent features of malignancies (32). Integrins promote various adhesion-dependent effects in tumor cells, including proliferation, survival, migration, and invasion through focal adhesion kinase (FAK) signaling cascades (33)(34)35). FAK phosphorylation is considered to be one of the initial steps that allows binding of Src and Fyn for further phosphorylation leading to signaling cascade (14,(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…3,8,20,21 In particular, integrin-β5 chain is required for TGF-β-induced EMT 8 and myofibroblast conversion. 22 Recent studies have also Integrin-β5 and zyxin mediate formation of ventral stress fibers in response to transforming growth factor β implicated integrin-β5 in the tumorigenic and metastatic capacities of breast carcinomas 23 and pancreatic cancer cells. 24 The cytoplasmic domain of integrins serves as an anchor for actin fibers and a platform for the assembly of adhesomes and adhesion-mediated signaling.…”
Section: Introductionmentioning
confidence: 98%
“…30 Accordingly, integrin-β5-FAK-Src signaling contributes to tumorigenic potential of breast cancer cells. 23 In addition, integrin-β1 may also contribute to actin remodeling in response to TGF-β by mediating p38MAPK signaling. 21 Thus, integrins can mediate cell-matrix adhesion and actin remodeling induced by TGF-β, although the function of specific β-integrins and the organization of the TGF-β-induced actin fiber structures remain to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…6, A and B). Previous studies have independently reported that ERK1/2 or PREX1/Rac1 promotes anchorage-independent growth of breast cancer cells (10,36,37). To determine whether PREX1 promotes anchorage independent colony formation via Rac1-ERK1/2, soft agar studies were undertaken in MDA-MB-231-luc-D3H1 cells overexpressing PREX1 in the presence of a MEK1/2 inhibitor (U0126), Rac1 inhibitor (NSC23766), or DMSO (vehicle).…”
Section: Prex1 Regulates Cell Proliferation and Cyclin D1 And P21mentioning
confidence: 99%